An improved bait method for collecting Hymenoptera, especially social wasps (Vespidae: Polistinae) - Noll, Fernando Barbosa [UNESP]; Gomes, Bruno [UNESP] (Entomological Soc Brasil, 2009)
In this work, an alternative method for the capture of neotropical social wasps is described, which may supplement or replace the procedures commonly used in wasp surveys. The method was tested in a seasonal semideciduous forest in the northwest of São Paulo State, collecting a larger number of species and a greater abundance of social wasps and of other Hymenoptera than other methods also used in the same area, namely Malaise traps, bottle traps and meat baits. The proposed method was adapted from Wille (1962) who used an attractive solution based on water and honey for bee attraction. In here, the attractive Solution was based on water, salt and crystal sugar, and was effective in attracting bees and solitary wasps, but mainly social wasps, which is the group of interest for this report.

Neste trabalho é proposto método para a captura de vespas sociais neotropicais nos mais diferentes habitats e que pode substituir os métodos comumente utilizados em levantamentosfaunísticos de curto prazo. O método foi inicialmente testado em um fragmento defloresta estacionalsemidecidual no Noroeste do estado de São Paulo, obtendo sucesso na coleta de vespas sociais e também de outros grupos de Hymenoptera. Coletou um número maior de espécies e também maior abundância do que outros métodos utilizados na mesma área, como armadilhas Malaise, garrafas-armadilha e iscas de carne. O método desenvolvido baseou-se na proposta de Wille (1962), que utilizou uma solução atrativa, composta por água e mel, para a coleta de abelhas. Neste trabalho, substituiu-se o mel por açúcar e adicionou-se sal, obtendo sucesso na atração não apenas de vespas sociais, mas também de abelhas e vespas solitárias.
Método de Armadilha Melhorado para a Coleta de Hymenoptera, especialmente de Vespas Sociais (Vespidae: Polistinae)
Keywords: Diversity; Epiponini; survey; Seasonal semideciduous forest; Diversidade; Epiponini; levantamento; floresta estacional semidecidual